Juror characteristics on trial: Investigating how psychopathic traits, rape attitudes, victimization experiences, and juror demographics influence decision-making in an intimate partner rape trial - Lilley, Caroline; Willmott, Dominic; Mojtahedi, Dara (Frontiers in Psychiatry, 2023)
Introduction Trial by jury is a longstanding legal tradition used in common law jurisdictions to try the most serious of criminal cases. Yet, despite hearing the same trial evidence, individual jurors often arrive at different verdict decisions, indicating that they may be impacted by more than the evidence presented at trial. This study therefore sought to investigate the role of jurors’ psychopathology, attitudinal, experiential, and demographic characteristics upon individual verdict decisions. Methods Adopting an improved mock trial paradigm, 108 jury-eligible participants took part in one of nine identical 12-person mock trial simulations depicting a videotaped recreation of an intimate partner rape trial. Pre-trial, mock-jurors completed a psychosocial survey capturing their psychopathic personality traits (affective and cognitive responsiveness, interpersonal manipulation; egocentricity), rape myth beliefs, victimization experiences and demographics. Post-trial, jurors deliberated to reach a collective group decision and individual verdict decisions were recorded pre- and post-deliberation. Results Binary logistic regression analyses revealed rape myth beliefs and juror ethnicity were significantly related to verdict decisions both pre- and post-deliberation. Post-deliberation, decreased affective responsiveness (empathy) and experience of sexual victimization were also found to be significant predictors of guilty verdict selections. Discussion These findings indicate for the first time that within an intimate-partner rape trial, certain psychosocial traits, crime-specific attitudes, and experiences of sexual victimization appear to predispose juror judgments and decision-making even after group-deliberation. This study therefore has important implications for understanding how individual differences among jurors may impact rape trial verdict outcomes and the need for targeted juror reforms.